Xylosylation of Phenolic Hydroxyl Groups of the Monomeric Lignin Model Compounds 4-Methylguaiacol and Vanillyl Alcohol by Coriolus versicolor - Kondo, Ryuichiro (1993)
When 4-methylguaiacol (MeG), a phenolic lignin model compound, was added to a culture that was inoculated with Coriolus versicolor, it was bioconverted into 2-methoxy-4-methylphenyl β-d-xyloside (MeG-Xyl). The phenolic hydroxyl group of vanillyl alcohol was much more extensively xylosylated than the alcoholic hydroxyl group. When a mixture of MeG and commercial UDP-xylose was incubated with cell extracts of mycelia, transformation of UDP-xylose into MeG-Xyl was observed. This result suggested that UDP-xylosyltransferase was involved in the xylosylation of phenolic hydroxyl groups of lignin model compounds.